The determination of phosphate in seawater by reverse flow injection spectrophotometry - Li Hui; Zhang Xinshen; Yu Lingyun; Wang Li; Chen Shujuan (Reviews in Analytical Chemistry, 2012)
A simple, sensitive, accurate and portable reverse flow injection (rFIA) spectrophotometric method is proposed for the on-line determination of trace phosphate in seawater. In acid conditions, phosphate reacts with ammonium molybdate to form molybdophosphoric acid, which forms a soluble complex compound with ethyl rhodamine B in the presence of polyvinyl alcohol. The absorbance of the complex compounds was measured by optical detector at 585 nm. Chemical factors and rFIA variables affecting the system were also discussed. Under the optimal conditions, the calibration graph for phosphate was linear over the concentration range from 2.0 to 200.0 μg/l with a correlation coefficient of 0.9995. The detection limit was 0.05 μg/l; the relative standard deviation was 0.61% for a solution containing 50 μg/l phosphate (n=15). The recovery of phosphate from three samples ranged from 96.4 to 98.4% of the added amount. The results obtained for phosphate by the proposed rFIA spectrophotometric method were in very close agreement with those using the conventional method.